New insights into growth hormone action - Waters, M J; Hoang, H N; Fairlie, D P; Pelekanos, R A; Brown, R J (Journal of molecular endocrinology, 2006)
It has been 75 years since Evans and Long identified a somatic growth-promoting substance in pituitary extracts, yet it is only in the last 20 years that the molecular basis for this action has been established. Three key elements in this elucidation were the cloning of the GH receptor, the identification of Janus kinase (JAK) 2 as the receptor-associated tyrosine kinase, and the delineation of signal transduction and activators of transcription (STAT) 5a/b as the key transcription factor(s) activated by JAK2. The interaction between these three elements results in enhanced postnatal growth and is the subject of this review. We describe a new model for GH receptor activation based on subunit rotation within a constitutive dimer, together with the phenotype and hepatic transcript profile of mice with targeted knockins to the receptor cytoplasmic domain. These support a central role for STAT5a/b in postnatal growth.